Unmasking MEGF10 Myopathy: A Rare Cause of Sudden Respiratory Failure in a Young Adult - Kleiser, Benedict; Hackenbruch, Luise; Schittenhelm, Jens; Bornemann, Antje; Haack, Tobias; Grimm, Alexander; Martin, Pascal (Case reports in neurological medicine, 2025)
Sudden respiratory insufficiency is commonly attributed to cardiopulmonary causes but may also herald underlying neuromuscular disorders. In this context, rare diseases in particular pose significant diagnostic challenges. Here, we report on a 27‐year‐old woman who presented with unexplained respiratory insufficiency, proximal muscle pain, and weakness. Initially, she was found unconscious with severe hypoxemia (oxygen saturation 41%), low respiratory rate (4/min), and hypotension, requiring emergency intubation. After treatment for pneumonia, persistent hypercapnia and hypoxemia were noted. Two months later, she reported muscle pain, reduced strength when climbing stairs, and swallowing difficulties. Physical examination showed symmetrical proximal paresis in arms and legs (MRC 4/5), dependence on hand support for head lifting, and inability to rise from a squat unaided. Reflexes were symmetrically reduced. There were no signs of myotonia. Medical history included kyphoscoliosis; family history was noncontributory for muscular disorders. In this case, we provide guidance on navigating the multiplicity of neuromuscular differential diagnoses in case of respiratory failure in combination with peripheral weakness, leading to the final diagnose of MEGF10 myopathy in this case.